Composite catalyst of diatom-doped carbon nitride as well as preparation method and application of composite catalyst
By doping cobalt and transition metal atoms in carbon nitride, the activity and stability of the catalyst are improved, and the problem of low degradation efficiency of antibiotic pollutants in the prior art is solved, and an efficient and controllable antibiotic removal effect is achieved. Suitable for mass production.
Patent Information
- Application Number
- CN202411840567.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art has low efficiency in degradation of antibiotic pollutants in wastewater treatment, poor catalyst stability, and is not widely used.
By doping cobalt atoms and transition metal atoms in carbon nitride, the synergistic effect of the catalyst is improved, and the activity and stability of the catalyst are significantly improved, and the activity is adjusted by adjusting the doping ratio to improve controllability. This catalyst significantly improves the ability to remove antibiotic pollutants in water by efficiently activating peroxy monosulfate.
It has achieved efficient removal of antibiotic pollutants in water, with high activity, stability and controllability, suitable for large-scale production, and has low cost, pollution-free and simple operation.
Smart Images

Figure CN119425761A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to a diatomic-doped carbon nitride composite catalyst and a preparation method and application thereof. Background Art
[0002] In recent years, science and technology have continued to flourish, and antibiotics have been widely used in industry, agriculture, animal husbandry, and medicine. However, the large-scale use of antibiotics has brought extremely serious harm to the environment. Due to their special chemical structure, antibiotics are difficult to be completely metabolized by animals, plants, and humans, so they inevitably enter the environment.
[0003] In the related art, wastewater treatment mainly uses physical treatment methods, biological treatment methods, etc. However, the degradation efficiency of antibiotic pollutants is low, the application is not widespread, and the catalyst stability is poor.
[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0005] The technical task of the present application is to address the above deficiencies and provide a composite catalyst of diatomic-doped carbon nitride and a preparation method and application thereof. The present application dopes cobalt atoms and transition metal atoms into carbon nitride to improve the synergistic effect of the catalyst, thereby significantly improving the activity and stability of the catalyst; by adjusting the addition ratio of cobalt atoms and transition metal atoms, the activity of the catalyst can be effectively adjusted, thereby improving the controllability of the catalyst; by efficiently activating peroxymonosulfate, the ability of the catalyst to remove antibiotic pollutants in wastewater and sewage is significantly improved, and it has the advantage of efficiently removing antibiotic pollutants in water. The preparation methods of the present application are all completed by thermal polymerization, which has the advantages of low cost, no pollution, and simple operation, and is suitable for large-scale production.
[0006] To achieve the above objectives, this application provides the following technical solutions: According to one aspect of the present application, a diatomic-doped carbon nitride composite catalyst is provided, comprising a carbon nitride matrix and cobalt atoms and transition metal atoms uniformly embedded in the carbon nitride matrix.
[0007] In some embodiments, the transition metal atom is a nickel atom or a copper atom.
[0008] In some embodiments, the content of the cobalt atoms and the transition metal atoms in the composite catalyst is 0.5 wt %-2 wt %.
[0009] In some embodiments, the diatomic-doped carbon nitride composite catalyst can effectively remove antibiotics in water. Preferably, the antibiotics are sulfamethoxazole, sulfamethoxazole, tetracycline, oxytetracycline and ciprofloxacin.
[0010] According to another aspect of the present application, a method for preparing a diatomic-doped carbon nitride composite catalyst is also provided, comprising: grinding and mixing urea and a metal precursor in an agate mortar, transferring the mixed powder into a covered crucible, calcining the mixture in a muffle furnace, cooling the mixture to room temperature after calcination, washing the mixture with deionized water, and drying the mixture to obtain a diatomic-doped carbon nitride composite catalyst.
[0011] In some embodiments, the metal precursor is a mixture of cobalt acetylacetonate and nickel acetylacetonate; or, the metal precursor is a mixture of cobalt acetylacetonate and copper acetylacetonate.
[0012] In some embodiments, the crucible is a high temperature resistant ceramic crucible, the calcination temperature is 500-550°C, the calcination time is 2-4h, the calcination heating rate is 5-10°C / min, and the drying temperature is 40-80°C.
[0013] According to another aspect of the present application, there is also provided an application of a diatomic-doped carbon nitride composite catalyst in the treatment of pharmaceutical wastewater, industrial wastewater and hospital wastewater.
[0014] In some embodiments, the pH of pharmaceutical wastewater, industrial wastewater and hospital sewage is 5-9.
[0015] In some embodiments, the pharmaceutical wastewater, industrial wastewater and hospital sewage contain sulfonamides, tetracyclines and quinolone antibiotics.
[0016] Compared with the prior art, the advantages and positive effects of this application are: 1. The present application doped cobalt atoms and transition metal atoms into carbon nitride to enhance the synergistic effect of the catalyst, thereby significantly improving the activity and stability of the catalyst.
[0017] 2. The present application can effectively adjust the activity of the catalyst by adjusting the addition ratio of cobalt atoms and transition metal atoms, thereby improving the controllability of the catalyst.
[0018] 3. The composite catalyst of the present application significantly improves the ability of the catalyst to remove antibiotic pollutants in wastewater and sewage by efficiently activating peroxymonosulfate, and has the advantage of efficiently removing antibiotic pollutants in water.
[0019] 4. The preparation methods of the present application are all completed by thermal polymerization, which has the advantages of low cost, no pollution, simple operation, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 The SEM image of the cobalt-nickel diatom-doped carbon nitride composite catalyst prepared in Example 1 of the present application is shown.
[0022] Figure 2 The SEM image of the cobalt-copper diatom-doped carbon nitride composite catalyst prepared in Example 2 of the present application is shown.
[0023] Figure 3 The TEM image of the cobalt-nickel diatom-doped carbon nitride composite catalyst prepared in Example 1 of the present application is shown.
[0024] Figure 4 The TEM image of the cobalt-copper diatom-doped carbon nitride composite catalyst prepared in Example 2 of the present application is shown.
[0025] Figure 5 The graph shows the results of the activity test of the catalysts prepared in Experimental Example 1 and Comparative Examples 1-4 of the present application for degrading sulfamethoxazole (SIZ).
[0026] Figure 6 The graph shows the results of the activity test of the catalysts prepared in Experimental Example 2 and Comparative Examples 1-4 of the present application for degrading sulfamethoxazole (SIZ).
[0027] Figure 7 The kinetic constants of the reaction of PMS activated with sulfamethoxazole prepared in Experimental Example 1 and Comparative Examples 1-4 of the present application are shown.
[0028] Figure 8 The kinetic constants of the reaction of PMS activated by the catalyst prepared in Experimental Example 2 and Comparative Examples 1-4 of the present application to sulfamethoxazole are shown.
[0029] Fig. 9 The degradation data of the cobalt-nickel diatomic doped carbon nitride composite catalyst at different pH values in Experimental Example 1 of the present application are shown.
[0030] Fig.10 The degradation data of the cobalt-copper diatomic doped carbon nitride composite catalyst at different pH values in Experimental Example 2 of the present application are shown.
[0031] Fig.11The diagram shows the catalytic removal effect of different organic pollutants on PMS activated by the cobalt-nickel diatomic doped carbon nitride composite catalyst in Experimental Example 1 of the present application.
[0032] Fig.12 The diagram shows the catalytic removal effect of different organic pollutants on PMS activated by the cobalt-copper diatomic doped carbon nitride composite catalyst in Experimental Example 2 of the present application.
[0033] Fig.13 The data graph of SIZ degradation activity of the carbon nitride composite catalyst doped with different doping amounts of cobalt-nickel diatomics in Comparative Example 5 of the present application is shown.
[0034] Fig.14 The data graph of SIZ degradation activity of cobalt-copper diatomic doped carbon nitride composite catalyst with different doping amounts in Comparative Example 5 of the present application is shown.
[0035] Fig.15 The data graph of SIZ degradation activity of the cobalt-nickel diatomic doped carbon nitride composite catalyst is shown in the case where no PMS is added in Comparative Example 6 of the present application.
[0036] Fig.16 The data graph of SIZ degradation activity of the cobalt-copper diatomic doped carbon nitride composite catalyst is shown in the case where no PMS is added in Comparative Example 6 of the present application.
[0037] Fig.17 The activity data graph of SIZ degradation when only PMS is added in Comparative Example 7 of the present application is shown. DETAILED DESCRIPTION
[0038] In order to more clearly understand the above-mentioned purposes, features and advantages of the present application, the present application is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0039] The present application is further described below in conjunction with the accompanying drawings and specific embodiments.
[0040] Embodiment 1: (1) Grind 10 g of urea, 10 mg of cobalt acetylacetonate, and 30 mg of nickel acetylacetonate in an agate mortar for 1 h, and transfer the ground powder to a crucible with a lid.
[0041] (2) The crucible was placed in a muffle furnace and calcined for 2 h at a temperature of 550 °C and a heating rate of 5 °C / min. After cooling to room temperature, it was washed five times with deionized water. The obtained product was dried in a vacuum oven at a temperature of 60 °C to obtain Co 0.5 Ni 2 -NC. The subscript represents the mass percentage of the metal measured by ICP-MS.
[0042] Embodiment 2: 10 g urea, 10 mg cobalt acetylacetonate and 30 mg copper acetylacetonate were put into an agate mortar and ground for 1 h. The other steps were the same as those in Example 1 and will not be repeated here. Co 0.5 Cu 2 -NC.
[0043] like Figure 1-2 As shown, Co 0.5 Cu 2 -NC、Co 0.5 Ni 2 -NC morphologies are all twisted and curled structures.
[0044] like Figure 3-4 As shown in the TEM image, Co 0.5 Cu 2 -NC and Co 0.5 Ni 2 -NC presents a structure composed of rolled sheets.
[0045] Comparative Example 1: NC was prepared according to the method of Example 1, except that no metal precursor was added.
[0046] Comparative Example 2: Co was prepared according to the method of Example 1 0.5 -NC, which is different from Example 1 in that nickel acetylacetonate or copper acetylacetonate is not added.
[0047] Comparative Example 3: According to the method of Example 1, Ni 2 -NC, which is different from Example 1 in that cobalt acetylacetonate is not added.
[0048] Comparative Example 4: Prepare Cu according to the method of Example 2 2 -NC, which is different from Example 2 in that cobalt acetylacetonate is not added.
[0049] Embodiment 3: The diatomic doped carbon nitride composite catalysts prepared in Examples 1-2 and Comparative Examples 1-4 were used to activate peroxymonosulfate (PMS), and the removal rate of sulfisoxazole (SIZ) was detected.
[0050] Detection method: The concentration of sulfisoxazole is 5ppm. Take 100mL of sulfisoxazole solution and place it in a beaker. Add 0.1mM PMS solution and use H 2 SO 4or NaOH to adjust the pH to 7.0, place the reactor at room temperature, the reaction temperature is 25°C, add 5 mg of NC, Co 0.5 -NC、Cu 2 -NC、Ni 2 -NC、Co 0.5 Cu 2 -NC、Co 0.5 Ni 2 -NC composite catalyst was mixed evenly. Then, 1 ml of the reaction solution was taken at regular intervals, and after the reaction was completed, the reaction system was separated using a 0.22 um filter membrane, and the concentration of sulfadiazole in the solution was determined using high performance liquid chromatography, and the removal rates of sulfadiazole by different catalysts were calculated.
[0051] like Figure 5-6 As shown, after 3min and 5min of reaction, Co 0.5 Cu 2 -NC and Co 0.5 Ni 2 -NC catalyst showed extremely efficient removal ability, with a removal rate of up to 100%. 0.5 -NC and Cu 2 -NC、Ni 2 The -NC materials are in stark contrast and show significant differences.
[0052] like Figure 7-8 As shown, from the perspective of reaction kinetics, Co 0.5 Cu 2 The reaction kinetic constant k of -NC reached 1.98 min⁻¹, which indicates that its reaction rate is fast, which is 49.5 times that of NC (0.04 min⁻¹) and is 2 -19.8 times of NC (0.10 min⁻¹) and Co 0.5 -NC (0.34 min⁻¹) is 5.82 times. 0.5 Ni 2 The reaction kinetic constant k of -NC reached 1.03min⁻¹, which is 25.8 times that of NC (0.04 min⁻¹) and Ni 2 -NC (0.06 min⁻¹) is 17.1 times that of Co 0.5 -NC (0.34min⁻¹). These differences in reaction rate constants clearly demonstrate the significant effect of diatomic doping, which greatly improves the catalytic activity, especially in the activation of peroxymonosulfate, which undoubtedly enhances the overall performance and practical value of the catalyst. The presence of diatoms not only improves the electronic structure and surface properties of the material, but also increases the number and types of active sites.
[0053] Embodiment 4: The diatomic doped carbon nitride composite catalyst prepared in Example 1-2 was used to detect the degradation performance of sulfamethoxazole by activating PMS at different pH values.
[0054] Detection method: The concentration of sulfisoxazole is 5 ppm. Take 100 mL of the solution and place it in a beaker. Add PMS solution (concentration is 0.1 mM) and use H 2 SO 4 or NaOH to adjust pH to 3.0, 5.0, 7.0, 9.0 and 11.0, place the reactor at room temperature, the reaction temperature is 25 ℃, add 5 mgCo 0.5 Cu 2 -NC、Co 0.5 Ni 2 -NC nanomaterials were mixed evenly. Then, 1.5 ml of the reaction solution was taken at regular intervals, and the reaction system was separated using a 0.22 um filter membrane after the reaction was completed. The concentration of sulfadiazole in the solution was determined using high performance liquid chromatography, and the removal rates of sulfadiazole by different catalysts were calculated.
[0055] like Figure 9-10 As shown, as the pH value increases from 3.0 to 7.0, Co 0.5 Cu 2 -NC、Co 0.5 Ni 2 -NC gradually increased the degradation of sulfisoxazole; it is worth noting that between pH 5.0 and 7.0, Co 0.5 Cu 2 -NC、Co 0.5 Ni 2 -NC degradation capacity can reach 100% within 3min and 5min respectively; when pH > 7.0, the degradation amount of sulfamethoxazole begins to decrease. 0.5 Cu 2 -NC、Co 0.5 Ni 2 -NC composite catalyst is most suitable for sewage and wastewater treatment processes in the pH range of 5 to 9.
[0056] Embodiment 5: The performance of degrading and removing multiple antibiotics was tested using the diatomic-doped carbon nitride composite catalyst prepared in Example 1-2.
[0057] In this example, a variety of common antibiotics were selected as representative contaminants for testing. These antibiotics cover several common medicines: sulfisoxazole (SIZ) and sulfamethoxazole (SMX) represent sulfonamides, tetracycline (TC) and oxytetracycline (OTC) represent tetracyclines, and ciprofloxacin (CIP) represents quinolones.
[0058] Degradation tests were performed under standardized conditions, with the reaction time uniformly set at 10 minutes. Figure 11-12 As shown in the figure, the above antibiotics were removed very efficiently within 10 minutes. Specifically, except for ciprofloxacin, the removal rates of the other antibiotics were all over 80%. Although ciprofloxacin performed slightly worse, its removal rate also reached 60%, which shows that even when facing pollutants with more complex structures or difficult to degrade, Co 0.5 Cu 2 -NC、Co 0.5 Ni 2 -NC still has strong catalytic ability. These results fully verify that Co 0.5 Cu 2 -NC、Co 0.5 Ni 2 The remarkable potential of NC catalysts in removing complex chemical pollutants from water, especially the high efficiency in such a short reaction time, highlights its value in practical water treatment applications.
[0059] Comparative Example 5: Detection of adding different masses of nickel acetylacetonate or copper acetylacetonate.
[0060] The composite catalyst was prepared according to the steps in Example 1, except that different masses of copper acetylacetonate or nickel acetylacetonate were added to successfully prepare Co 0.5 Cu 0.2 -NC (add 5 mg copper acetylacetonate), Co 0.5 Cu 0.5 -NC (add 10 mg copper acetylacetonate), Co 0.5 Cu 1 -NC (20 mg of copper acetylacetonate added) and Co 0.5 Ni 0.2 -NC (5 mg nickel acetylacetonate added), Co 0.5 Ni 0.5 -NC (10 mg nickel acetylacetonate added), Co 0.5 Ni 1 -NC (20 mg nickel acetylacetonate added).
[0061] The above composite catalyst was tested using the method for testing the removal rate in Example 3, such as Figure 13-14 As shown, its degradation efficiency is comparable to that of Co0.5 Cu 2 -NC、Co 0.5 Ni 2 -NC is obviously lower, which indicates that the content of copper acetylacetonate or nickel acetylacetonate doping is very important to improve the catalytic activity.
[0062] Comparative Example 6: like Figure 15-16 As shown, when peroxymonosulfate (PMS) was not added during the reaction, the Co 0.5 Cu 2 -NC、Co 0.5 Ni 2 -NC materials have almost no degradation ability for sulfamethoxazole, achieving only 18% and 13% removal. This further emphasizes the importance of PMS as a synergistic catalyst, which significantly improves the performance of Co in the reaction. 0.5 Cu 2 -NC、Co 0.5 Ni 2 -NC degradation ability.
[0063] Comparative Example 7: like Fig.17 As shown, when the prepared catalyst was not added during the reaction and only peroxymonosulfate (PMS) was added, the study observed that in the absence of catalyst activation, PMS had almost no degradation ability on sulfamethoxazole and could only achieve 5% removal, which illustrates the activation effect of the catalyst on PMS to degrade antibiotic pollutants.
[0064] Through the above specific implementations, those skilled in the art can easily implement the present application. However, it should be understood that the present application is not limited to the above specific implementations. Based on the disclosed implementations, those skilled in the art can arbitrarily combine different technical features to achieve different technical solutions.
Claims
1. A diatomic doped carbon nitride composite catalyst, characterized in that: The invention comprises a carbon nitride matrix and cobalt atoms and transition metal atoms uniformly embedded in the carbon nitride matrix.
2. The diatomic-doped carbon nitride composite catalyst according to claim 1, characterized in that: The transition metal atom is a nickel atom or a copper atom.
3. The diatomic-doped carbon nitride composite catalyst according to claim 1, characterized in that: The content of the cobalt atoms and the transition metal atoms in the composite catalyst is 0.5wt%-2wt%.
4. The diatomic-doped carbon nitride composite catalyst according to claim 1, characterized in that: The diatomic-doped carbon nitride composite catalyst can effectively remove antibiotics in water. Preferably, the antibiotics are sulfamethoxazole, sulfamethoxazole, tetracycline, oxytetracycline and ciprofloxacin.
5. The method for preparing a diatomic-doped carbon nitride composite catalyst according to claim 1, characterized in that: include: The urea and the metal precursor are ground and mixed in an agate mortar, the mixed powder is transferred to a covered crucible, and the mixture is calcined in a muffle furnace. After calcination, the mixture is cooled to room temperature, washed with deionized water, and dried to obtain a diatomic-doped carbon nitride composite catalyst.
6. The method for preparing a diatomic-doped carbon nitride composite catalyst according to claim 5, characterized in that: The metal precursor is a mixture of cobalt acetylacetonate and nickel acetylacetonate; or, the metal precursor is a mixture of cobalt acetylacetonate and copper acetylacetonate.
7. The method for preparing a diatomic-doped carbon nitride composite catalyst according to claim 5, characterized in that: The crucible is a high temperature resistant ceramic crucible, the calcination temperature is 500-550°C, the calcination time is 2-4h, the calcination heating rate is 5-10°C / min, and the drying temperature is 40-80°C.
8. Use of the diatomic-doped carbon nitride composite catalyst according to any one of claims 1 to 7 in the treatment of pharmaceutical wastewater, industrial wastewater and hospital sewage.
9. The use according to claim 8, characterized in that: The pH value of pharmaceutical wastewater, industrial wastewater and hospital sewage is 5-9.
10. The use according to claim 8, characterized in that: The pharmaceutical wastewater, industrial wastewater and hospital sewage contain sulfonamides, tetracyclines and quinolone antibiotics.